1990
DOI: 10.1210/endo-126-5-2288
|View full text |Cite
|
Sign up to set email alerts
|

Release of Substance P from Rat Hypothalamus and Pituitary by Endothelin

Abstract: Endothelin-1 is a 21 amino acid peptide originally isolated from porcine aortic endothelium and has recently been localized within the central nervous system. We have administered endothelin-1 in a dynamic perfusion system in order to study its possible effects on the rat hypothalamus and anterior pituitary. Tissue (hypothalami or quartered pituitaries) was placed into plastic chambers and was perfused with oxygenated Krebs-bicarbonate solution. After an interval to establish stable basal peptide release, endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…ET peptides may be involved in the control of vasopressin and oxytocin release from the posterior pituitary (19) and have been shown to promote the release of vasopressin and substance P from hypothalamic slices (27,28) and of luteinizing hormone, follicle-stimulating hormone, and substance P from pituitary cells (15,28 …”
mentioning
confidence: 99%
“…ET peptides may be involved in the control of vasopressin and oxytocin release from the posterior pituitary (19) and have been shown to promote the release of vasopressin and substance P from hypothalamic slices (27,28) and of luteinizing hormone, follicle-stimulating hormone, and substance P from pituitary cells (15,28 …”
mentioning
confidence: 99%
“…These siological effects on the central nervous system as an autacoid, neurotransmitter or neuromodulator. ET stimulates substance P release from rat hypothalamus and pituitary [ 12] and inhibitis prolactin release from rat pituitary [ 13] in vitro. In the present study, ET stimulated PGE2 release from the rat ME.…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, we have shown that these peptides are recognized by the GnRH receptor (Table 3). Furthermore, these ET antagonists stimulate LH release, which is surprising because these peptides are expected to inhibit the ET-induced activation of LH release via the ET A receptor (Calvo et al, 1990;Stojilkovic et al, 1992). A GnRH antagonist (Fig.…”
Section: Discussionmentioning
confidence: 99%